National Audubon Society checklist, Karen Drews, January 6 1986 - Drews, K. L.et al (1986)
Checklist dated January 6, 1986 compiled by Karen Drews. A list birds sighted by Drews and 26 others at De Soto National Wildlife Refuge. A total of 56 species and 32,955 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed